Constitutionality of Simultaneous Extension and Renewal of Land Rights - Mahfud, Muh Afif; Djohan, Naufal Hasanuddin; Malik, Muhammad Fahad (Magister of Law, Faculty of Law, University of Mataram, 2024)
One form of state control is to regulate the granting of land rights, including determining the subject of the right and the duration of a land right. The determination of the period of land rights must pay attention to equality of opportunity and access in acquiring and controlling land so as to create the greatest prosperity of the people as the goal of national agrarian law. This is a normative research that focuses on examining the harmony between regulations so that it uses a statute approach and conceptual approach. Therefore, primary legal materials and secondary legal materials obtained based on literature research are used. The data obtained was then analyzed based on content analysis. In this research, it is found that there are overlapping regulations between the Basic Agrarian Law, Governmental Regulation No. 40 of 1996, Agrarian Minister Regulation No. 18 of 2021 and Government Regulation No. 12 of 2023 regarding the extension and renewal of land rights at the same time. In addition, in reality, the simultaneous extension and renewal of land rights causes several things, namely: (1) legal uncertainty because there are regulations as the basis that collide with each other; (2) inequality and injustice for the community in accessing land; and (3) presents unconstitutionality because basically this policy has violated the Constitutional Court's decision.